Women empowerment in political institutions : an Indian perspective - National Conference on "Empowerment of Women in Parliament and Local Self-Government Institutions in India : Role, Status, Participation and Decision Making" (2008 : Tirupati, India); Sundar Ram, D. 1960-; Academy of Grassroots Studies and Research, India (New Delhi : Academy of Grassroots Studies and Research of India, Tirupati (A.P.) by Kanishka Publishers, Distributors, 2009)
Papers presented at the National Conference on Empowerment of Women in Parliament and Local Self-Government Institutions in India : Role, Status, Participation and Decision Making, held at Tirupati during 19-20 August 2008.
Includes bibliographical references (p. [256]-272) and index.
Keywords: Women -- Political activity -- India -- Congresses; Women in development -- India -- Congresses